Control interno en el departamento de producción y su efecto en la rentabilidad de la Empresa Balitsa S.A. 2017 - Aldas Cando, Ingrid Narcila (2018)
By means of this project discussed the current situation in terms of the process of internal control in the Department of production and its effect on the profitability of the company BALITSA S.A., for the year 2017. Mentioned private family-run company is dedicated to the activities of cultivation and development of wood products in general. It has areas for receipt of timber, production, administration and sales. This research work, was based on deficiency control or the realization of an empirical control of production activities, which directly affects the profitability generated in processes before exposed. For which, established goals that allowed to analyze and evaluate the current situation of the company, by using a sheet of evaluation of internal control, financial statements, an interview and a survey of the staff working there. The methodologies and tools used in this research, such as inductive and deductive method, the use of books, manuals, reference theses, among others, allowed to collect information necessary to learn how they manage the productive area and cost-effective BALITSA S.A. results thanks to the interview the owner manager and the survey executed 20 employees, concluding that this does not have a management report, employees not are evaluated frequently in their activities and there is a deficiency in the area of production control. In addition, the internal control assessment determined that the risk level is medium and that their level of profitability is not so positive compared to the accounting period of 2016, resulting in that does not meet long-term goals established production and end up affecting the economy of the company. As part of the recommendation proposes the company implement a Handbook of management and control oriented towards the needs of the business in order to improve specific areas and employment of workers. Keywords: Profitability, management, internal control audit.